Implementasi Terapi Kompres Jahe Berbasis Kearifan Lokal Untuk Mencegah Rheomatoid Arthritis Di RT 05 Kelurahan Senalang Kota Lubuk Linggau - Popy Alpinda; Siti Anisa; Wilanti Astuti; Yutha Octaviani; Yuli Eka Damai Yanti; Taufiani Rossita (Utami Publisher, 2026)
Rheumatoid Arthritis (RA) is a chronic inflammatory disease commonly experienced by the elderly and impacts a decreased quality of life due to pain and limited mobility. RA treatment focuses not only on pharmacological therapy but also non-pharmacological therapies such as ginger compresses and rheumatic exercises. This study aims to determine the effect of counseling and demonstrations of ginger compresses and rheumatic exercises on increasing knowledge and reducing joint pain in the elderly in RT 05, Senalang Village. The method used was a pretest-posttest through counseling and demonstration activities. The results showed an increase in the elderly's knowledge from sufficient to good after the intervention. This activity is effective as a promotive and preventive effort in managing RA in the community.